Integrating Experiential Learning in the Virtual Translation Classroom - Sazdovska-Pigulovska, Milena (Hankuk University of Foreign Studies (HUFS) in Seoul, South Korea, 2021)
The introduction of blended learning in translation and interpreting education in Europe has resulted in tremendous changes, such as transiting from traditional translation classrooms to student-centered learning and digital eco-systems for translation as well as switching from traditional learning to experiential learning. Experiential learning is learning through experience, direct involvement and collaboration, whereas it plays a great role in translation and interpreting studies. Experiential education is based on the Experiential Model Theory (Kolb 1984; 2015) and finds application in translation studies (Kiraly; Hofmann 2005). The translator profession is interdisciplinary and translator competences expand beyond linguistic skills, and also require transcultural and communication skills, thematic skills, intrapersonal and interpersonal skills, digital skills and other soft skills (EMT 2017). The purpose of integrating experiential learning in the translation classroom is to enable translators to learn from real life experience, thus acquiring future professional skills. However, the shift to virtual translation classrooms due to the global Covid-19 pandemic makes in increasingly difficult to create a virtual collaborative environment, to implement online project-based learning, to teach digital skills online, to apply emotional intelligence in a virtual translation classroom or to conduct internship in relevant institutions. This paper aims to discuss the main challenges of experiential learning after switching to online education and to suggest alternatives to experiential learning in a virtual translation classroom.
Keywords: experiential learning, translation, translator competences, virtual collaborative environment